The Influence of a Scientific Approach on Critical Thinking and Logical Thinking Abilities in Early Childhood - Muhammad Arifin Sitorus (ATTAQWA: Jurnal Pendidikan Islam dan Anak Usia Dini, 2024)
Objective study this is for know influence approach scientific to ability think logical on child age early And know influence approach scientific to ability think critical on child age early in the Village Marindal I District Patumbak Deli Serdang Regency . The population in this study were all Raudhatul Athfal in Marindal I Village, Patumbak District, Deli Serdang Regency, consisting of 7 Raudhatul Athfal group B in Marindal I Village, Patumbak District, Deli Serdang Regency. Specifically, this research was conducted on children aged 5-6. The time for carrying out the research is adjusted to the learning program, namely in the odd semester of the 2023/2024 academic year. The sample is determined using random sampling, where each population has the right to be selected as a sample. However, to choose them you can use a random lottery which determines the two samples in this study for research purposes. One Way Analysis of Variance is a powerful analysis technique for testing differences in means with many randomly selected groups. Hypothesis testing in One Way Analysis of Variance is carried out using F-test statistics. Results study stated that 1) There is an influence of the scientific learning approach on the critical thinking abilities of young children . The results of the data on children's critical thinking abilities have a calculated t value ( 5.016 )> t table (1.671) and sig.2-tailed (0.000) <α=0.05. 2) There is an influence of the scientific learning approach on the logical thinking abilities of young children . Data on children's logical thinking abilities has a calculated t value ( 2.708)> t table (1.671) and sig.2-tailed (0.000)<α=0.05.